The Photoroom application and Google Business Profile are used to Optimize digital marketing for SMEs in Bugangan Village. - Menarianti, Ika (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Bugangan has a strategic location and is easily accessible. Its diverse community supports social and economic dynamics. In 2023, 112 MSMEs are operating in the area. SMEs have a positive impact on the economic development of the community. SME operators need skills in using applications and online platforms to create marketing content and provide customers with complete information. This activity is a Community Service initiative aimed at reducing income disparities among residents. The proposed method involves mentoring and training for SME operators in Bugangan Village. Business operators are encouraged to analyze the current market conditions to identify changes in customer behavior. Mentoring and training will provide skills in creating marketing content using the Photoroom application. The resulting marketing content will then be uploaded to serve as a business profile. Business operators will also practice using the Google Business Profile platform to enhance their business visibility. This activity is expected to help business operators offer and market their products online.